2015
DOI: 10.1080/15710882.2015.1054841
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sketch types on distributed design team work

Abstract: (2015). Influence of sketch types on distributed design team work. CoDesign, 11(2), pp. 99-118. doi: 10.1080/15710882.2015.1054841 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent Influence of Sketch Types on Distributed Design Team WorkProduct development is a collaborative activity more often than ever carried out by distributed design teams. It is critical to determine how sketches are used in such environments in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Another approach has been to classify sketches. While detailed typologies illustrate the purposes of design sketches (see the review in Schembri et al, 2015), they fall short of recognising whether a single sketch serves multiple functions (van der Lugt, 2005) and of explaining the unfolding activities along the timeline.…”
Section: Collaboration and Interaction In Collaborative Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach has been to classify sketches. While detailed typologies illustrate the purposes of design sketches (see the review in Schembri et al, 2015), they fall short of recognising whether a single sketch serves multiple functions (van der Lugt, 2005) and of explaining the unfolding activities along the timeline.…”
Section: Collaboration and Interaction In Collaborative Designmentioning
confidence: 99%
“…Focusing on the complete design process, Schembri et al (2015) suggested that sketches produced to share and explain an idea are crucial in promoting collaboration and decision-making. Two more detailed approaches recognised sketching-related patterns, yet of a very different character.…”
Section: Sketching In Collaborative Designmentioning
confidence: 99%
“…Also, sketches have been used by designers working with designers from other disciplines (Schembri et al . ). Sketching and drawing can communicate meaning quickly and easily; because of these characteristics, these methods can be a vehicle that exercises the imagination and builds interaction between different people (Buston ).…”
Section: Introductionmentioning
confidence: 97%
“…In the drawing process, the drawn mark acquires meaning (Adams 2001), and several researchers have investigated how drawing and sketching can be used as a good communication tool for children who particularly struggle to express their thoughts and feelings to other people because of their young age or due to severe illness (Hajdar 2015;Malchiodi 1998;Rollins 2005;Rubin 1984). Also, sketches have been used by designers working with designers from other disciplines (Schembri et al 2015). Sketching and drawing can communicate meaning quickly and easily; because of these characteristics, these methods can be a vehicle that exercises the imagination and builds interaction between different people (Buston 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Early-phase ideation is fundamental to product and industrial design processes. Ideation involves divergent thinking for quick externalization of ideas to help the designer understand the design problem [18,23]. This exploratory nature of ideation demands an uninhibited flow between what a designer is thinking and what the designer is doing to communicate the thought.…”
mentioning
confidence: 99%